2021
DOI: 10.1097/cce.0000000000000395
|View full text |Cite
|
Sign up to set email alerts
|

Early Tocilizumab Dosing Is Associated With Improved Survival in Critically Ill Patients Infected With Severe Acute Respiratory Syndrome Coronavirus-2

Abstract: Objectives: To identify the most efficacious timing for tocilizumab administration in critically ill patients infected with severe acute respiratory syndrome coronavirus-2. Design: Observational multicenter cohort study. Setting: A total of 23 acute care hospitals in four states. Patients: One-hundred eighteen patients admitted between March 13, 2020, and April 16, 2020. Eighty-one patients received tocilizumab, and 37… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 11 publications
3
15
0
1
Order By: Relevance
“…These are known independent risk factors for death [ 16 ]. Immunotherapy with tocilizumab in the first 36 h (early initiation) was an independent predictor for survival with an HR = 0.52 (95% CI: 0.28–0.97, p = 0.041) and a similar observation was made in another study [ 33 ]. NLR was found to have independent predictive value for death in a meta-analysis with a reported relative risk (RR) of 2.74 (95% CI: 0.98–7.66) regardless of the cut-off values used [ 24 ], and this result is in line with the hazard ratio we described earlier for an NLR > 11.…”
Section: Discussionsupporting
confidence: 78%
“…These are known independent risk factors for death [ 16 ]. Immunotherapy with tocilizumab in the first 36 h (early initiation) was an independent predictor for survival with an HR = 0.52 (95% CI: 0.28–0.97, p = 0.041) and a similar observation was made in another study [ 33 ]. NLR was found to have independent predictive value for death in a meta-analysis with a reported relative risk (RR) of 2.74 (95% CI: 0.98–7.66) regardless of the cut-off values used [ 24 ], and this result is in line with the hazard ratio we described earlier for an NLR > 11.…”
Section: Discussionsupporting
confidence: 78%
“…Why the human data sets all failed to provide a z-score for tocilizumab (Supplemental Table 6) is unclear, given the clear IL-6 signatures (Figure 4A,B). Conceivably, the human lung samples were collected too late, with the best results for tocilizumab achieved when the drug was given early in infection (50). Overall these results argue that K18-hACE2 mice represent a suitable model in which to test biologics and chemotherapeutics for COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Identifying patients with rapidly developing pneumonia and a high risk of developing acute respiratory distress syndrome (ARDS) as soon as possible might help individualize pharmacological treatment and optimal utilization of medical resources. It was demonstrated that the sooner pharmacological treatment is started in such patients, the greater are the chances of survival [ 15 , 16 , 17 , 18 ]. We found that patients with more extensive lung changes on admission objectified by a higher TSS were likely to present with fever, had decreased finger oxygen saturation and arterial oxygen partial pressure, increased laboratory indicators of inflammation including serum c-reactive protein and ferritin, and decreased lymphocytes count.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HD patients are characterized by impaired innate immunity and a worse humoral and cellular response to vaccines than in the general population [ 12 , 13 , 14 ]. Various methods of pharmacological treatment, including inhaled steroids, casirivimab-imdevimab, remdesivir, and tocilizumab are highly hoped for, which, as research shows, if applied early enough, can significantly improve the prognosis [ 15 , 16 , 17 , 18 ]. Therefore, the need to identify patients infected with SARS-CoV-2 and those who develop pneumonia, which may be fatal or have persistent sequelae, remains as urgent as possible.…”
Section: Introductionmentioning
confidence: 99%